PP RI No.25 Th.2000 ttg kewenangan pemerintah dan kewenangan propinsi sbg daerah otonom - [Tidak Terdaftar] (NOVINDO PUSTAKA MANDIRI, 2000)
PP RI No.25 Th.2000 ttg kewenangan pemerintah dan kewenangan prop sbg da...